Zen and the art of business communication : a step-by-step guide to improving your business writing skills - Luck, Susan L. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
In today's online world, our professional image depends on our ability to communicate. Whether we're communicating by email, text, social media, written reports, or presentations, how we use our words often determines how others view us. This book offers tips and techniques that can improve anyone's professional image. It covers how to analyze your multiple audiences and strategies for communicating your message effectively for each; structuring your message for greatest readability and effect; persuasion and tone; and how to face your own fears of writing. The content is delivered in a simple, clear style that reflects the Zen approach of the title, perfect for both the entry-level employee and the seasoned executive.
1. Introduction -- 2. Honor focus -- 3. Honor purpose and identity -- 4. Honor your goals -- 5. Honor the audience -- 6. Honor the structure -- 7. Honor clarity -- 8. Embrace the fear -- 9. Honor the reader -- 10. Honor the positive -- 11. Honor the concrete -- 12. Honor the definite -- 13. Respect the flow -- 14. Honor truth -- 15. Know the devil in the details -- References -- Index.
Includes bibliographical references (pages 183-184) and index.
Title from PDF title page (viewed on August 29, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business writing; business communication; managerial communication; business writing; managerial writing; organizational communication; leadership communication; good writing; writing advice; grammar for business; writing for business; professional image; Electronic books